1999
DOI: 10.3109/10428199909058454
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Apoptosis-Controlling Proteins in Acute Leukemia Cells

Abstract: The expression of Bcl-2 family proteins (Bcl-2, Bcl-X, Bcl-XL, Bcl-Xs, BAX, BAD, MCL-1) and of Interleukin-1 converting enzyme (ICE)-related proteins (ICE, CPP32, ICH- 1) was analyzed in acute leukemia cells by flow cytometry. Most proteins studied were detectable in cell lines such as KG1a, HL60, K562 (myeloblastic), REH, RAJI and MOLT4 (lymphoblastic) and VAL (B-cell lymphoma). However, BCL-Xs and BAK were weakly expressed in K562, as were Bcl-X, BAD and BAK in the VAL line. In acute myeloid leukemia (66 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 25 publications
1
29
0
1
Order By: Relevance
“…There are several different mechanisms known to be involved in the development of MDR in human leukemia cell lines, including overexpression of the drug transporters Pglycoprotein (P-gp) or multidrug resistance-associated protein (MRP1), and alterations in apoptotic cell death mechanisms (Safa, 1998;Campos et al, 1993). We have found that PR3 expression is significantly decreased in the drug resistant HL-60 subline, HL-60/ ADR, compared to the sensitive HL-60 cells.…”
Section: Introductionmentioning
confidence: 57%
“…There are several different mechanisms known to be involved in the development of MDR in human leukemia cell lines, including overexpression of the drug transporters Pglycoprotein (P-gp) or multidrug resistance-associated protein (MRP1), and alterations in apoptotic cell death mechanisms (Safa, 1998;Campos et al, 1993). We have found that PR3 expression is significantly decreased in the drug resistant HL-60 subline, HL-60/ ADR, compared to the sensitive HL-60 cells.…”
Section: Introductionmentioning
confidence: 57%
“…While one study showed that high levels of procaspase 2 and 3 portended a poor survival in adult AML, other studies have found no relationship between the absolute levels of these proteins and outcome in both lymphoid and non-lymphoid disease. [32][33][34] Again, these discordant results may be related to the fact that baseline protein expression might not be reflective of enzyme activity that is induced upon exposure of leukemic cells to therapy. Estrov et al 32 found that the levels of cleaved (and presumably active) caspase-3 correlated with a favorable outcome in AML.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins are potent inhibitors of cell death, and high expression levels are observed in many cancers (Adams and Cory, 1998;Reed, 1999). Bcl-2 itself is highly expressed in the majority of cases of acute leukaemia, approximately 50% of diffuse large B-cell lymphomas and up to 90% of malignant melanomas (Banker et al, 1997;Jansen et al, 1998;Campos et al, 1999;Skinnider et al, 1999). Forced expression of Bcl-2 results in resistance to a variety of proapoptotic stimuli, including growth factor withdrawal, cytotoxic chemotherapy and radiation, and there is some evidence that Bcl-2 also promotes resistance to anticancer immune responses.…”
mentioning
confidence: 99%